2011
DOI: 10.1128/jvi.01818-10
|View full text |Cite
|
Sign up to set email alerts
|

Tupaia CD81, SR-BI, Claudin-1, and Occludin Support Hepatitis C Virus Infection

Abstract: Hepatitis C virus (HCV)-related research has been hampered by the lack of appropriate small-animal models. It has been reported that tree shrews, or tupaias (Tupaia belangeri), can be infected with serum-derived HCV. However, these reports do not firmly establish the tupaia as a reliable model of HCV infection. Human CD81, scavenger receptor class B type I (SR-BI), claudin 1 (CLDN1), and occludin (OCLN) are considered essential receptors or coreceptors for HCV cell entry. In the present study, the roles of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 47 publications
1
58
0
1
Order By: Relevance
“…This finding explains the recent observation that an HCV variant selected to utilize murine CD81 with efficiency equal to that of human CD81 was able to enter cells expressing only murine entry factors (4). In line with this, primary hepatocytes of the small mammal Tupaia belangeri were recently reported to be susceptible to HCVcc entry (39). Moreover, the alanine-to-glycine exchanges in positions 223 and 224 account for this difference in coreceptor efficiency, as was predicted by HCVpp assays (29), indicating that despite differences in particle architecture, HCVpp remain a model strongly predictive of the behavior of HCVcc.…”
Section: Discussionmentioning
confidence: 71%
“…This finding explains the recent observation that an HCV variant selected to utilize murine CD81 with efficiency equal to that of human CD81 was able to enter cells expressing only murine entry factors (4). In line with this, primary hepatocytes of the small mammal Tupaia belangeri were recently reported to be susceptible to HCVcc entry (39). Moreover, the alanine-to-glycine exchanges in positions 223 and 224 account for this difference in coreceptor efficiency, as was predicted by HCVpp assays (29), indicating that despite differences in particle architecture, HCVpp remain a model strongly predictive of the behavior of HCVcc.…”
Section: Discussionmentioning
confidence: 71%
“…Current studies suggest that a total of 163 human genes were reported to respond in HBV and HCV infection 39,40 . The counterparts of most of those genes are present in the tree shrew genome and shared a relatively high sequence identity with human ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3), in which recurrent viral antagonism has led to a convergent evolution of escape from hepaciviral antagonism in primates 42 . Note that a recent study by Tong et al 40 provided functional data that tree shrew CD81, SR-BI, claudin-1 and occludin support HCV infection.…”
Section: Resultsmentioning
confidence: 99%
“…Production and infection of Huh7.5.1 cells using infectious HCV JFH1 (a genotype 2a isolate) or murine leukemia virus-based HCVpp were performed as described (29,30). Pseudotyped particles harboring glycoprotein of the vesicular stomatitis virus (VSVGpp) onto murine leukemia virus were used as a control.…”
Section: Production Of Hcvppmentioning
confidence: 99%